HUBUNGAN PENDAPATAN TERHADAP POLA MAKAN TUKANG KEBUN DI UNIVERSITAS NEGERI MEDAN - Hanum, Yusfa; Siregar, Olga Utami (Universitas Negeri Medan, 2013)
ABSTRACT This study aims to determine the relationship of income with diet of gardeners at State University of Medan. The population of this study were all gardeners Medan State University who were 30 and drawn samples with total sampling number of 30 people consisting of 17 men - men and 13 women with with age 55-61 years.Data of the research were collected by distributing questionnaires to the income variable (X) and variable diet gardener (Y) by way of